The Influence of Organizational Culture on Work Discipline and Organizational Commitment at the Environmental Agency of Tarakan City - Ali Mahfudz; Majang Palupi (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the influence of organizational culture on work discipline and organizational commitment at the Environmental Agency of Tarakan City. The research employs both quantitative and qualitative approaches. Quantitative data were collected through questionnaires distributed to 125 respondents, while qualitative data were obtained through interviews with selected informants. Data analysis was conducted using PLS-SEM with the SmartPLS software. The findings indicate that organizational culture has a significant positive influence on work discipline and organizational commitment. This study provides recommendations for the Environmental Agency of Tarakan City to strengthen organizational culture by enhancing teamwork, disseminating policies effectively, and implementing a consistent reward system. The study's limitations include its focus on a single independent variable and two dependent variables, as well as its cross-sectional nature, which does not capture long-term dynamics. Future research is encouraged to explore additional variables that may influence work discipline and organizational commitment.